FEM modelling of the three stages of friction stir spot welding - Carr, Gustavo Eduardo (2023)
A three-dimensional modelling of the Friction Stir Spot Welding process was carried out by means of a two-dimensional continuum with symmetry of revolution around the tool axis. The model included the plunging, dwelling and withdrawal stages of two (Formula presented.) mm thick AA6061 alloy plates joining process. A highly viscous flow model was adopted, as well as the hypothesis of full stick contact between tool and material. The model was solved by means of the Finite Element Method (FEM) and Arbitrary Lagrangian Eulerian (ALE) techniques in an axisymmetric domain with mesh tracking and algorithms to account for contact and free flow. Numerical results were compared to experimental data found in literature. The maximum temperature for the pin front face was found within less than (Formula presented.) % of the experimental value. The velocity field were found close to those reported in literature and the final shape of the weld flash was similar to its experimental counterpart.